Ergebnisse und Probleme von Agrarreformen im Mittelmeerraum - Rother, Klaus (ERDKUNDE, 1971)
In his public inaugural lecture the author discusses the term 'agrarian reform' and goes into the most important causes of the agrarian reforms in the Mediterranean area. He sees these as lying in the inherited agrarian organisation, the vehement population growth and in the unfavourable natural conditions. Next, the general effects of reforming measures are outlined (extension of the oecumene, gathering together of scattered settlement, intensification of land use, strengthening of the peasant class, encouragement of industrialisation and tourism) and examined more closely in the examples of Italy, Tunisia and Israel. The differing success of agricultural colonisation seen in these countries is, in a closing comparative section, ascribed primarily to the strength of the prevailing spirit of enterprise in the various cases.